Pre-service physical education teachers’ perceptions of esports as a potential career pathway - Putra, Muarif Arhas; Manurizal, Lolia (UIR Press, 2024)
Background Problems: The world of sports and gaming has witnessed a significant transformation in recent years. Esports, which refers to competitive video gaming, has gained immense popularity among individuals of all ages. This article explores the perception of health and sports education pre-service teachers on esports, specifically focusing on Mobile Legend, PUBG Mobile, Crossfire, and Valorant as potential future professional careers. Research Objectives: The purpose of this research is to know the perception of health and sports education pre-service teachers on eSports as a future professional career. Methods: This study uses a mixed method to collect data through quantitative (questionnaire) and qualitative (focus group interviews) methods. There were 116 people with different backgrounds to fill out the form. The instruments used were a questionnaire and a discussion guide. The first instrument that was used was a questionnaire using a g-form, followed by discussion. The data analysis used Miles dan Huberman technique. Findings and Results: As a result, about the health and sport education pre-service teacher perception through esports, Mobile Legend placed first as the most played esports, followed by PUBG Mobile, Crossfire, and Valorants in the last place. 88.8% said that esports can be a professional career, with some of them already making money from playing the game. 94.82% of players playing esports are only for entertaining or filling free time, but most of them, especially the Mobile Legend players, understand the rules and the strategy to win the game. About 50.9% of online game addiction behaviours may occur among adolescents. Conclusion: As a conclusion, pre-service physical education teachers’ perceptions show that they believe that esports can be a potential career pathway.